2012
DOI: 10.4028/www.scientific.net/msf.706-709.2140
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Austenitization Temperature on the Mechanical Properties of a Prehardened Mould Steel

Abstract: The many practical difficulties and longer lead time with heat treatment of mould steels after machining have led to increased demand for steels in prehardened condition, typically ~ 40HRC. At this hardness the steel possesses an optimal combination of high strength and machinability. The steels used for moulds require a wide range of demanding properties, among which high enough strength and toughness are the primary necessities in order to resist any deformation and dimensional change in mould during use. Ud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…They have concluded that the hierarchical arrangement of packets/blocks and lath boundaries allows to accommodate the crystallographic shears of the transformation; this ensures that the net strain in the prior austenite grain is pure dilatation. Additionally, experimental evidence has shown that the prior-austenite grain size has a strong effect on the scale of packets and blocks and almost negligible effects on the lath substructure development [9][10][11][12]. This implies that the microstructure in the lath boundaries is practically independent of the prior-austenite grain size.…”
Section: Introductionmentioning
confidence: 92%
“…They have concluded that the hierarchical arrangement of packets/blocks and lath boundaries allows to accommodate the crystallographic shears of the transformation; this ensures that the net strain in the prior austenite grain is pure dilatation. Additionally, experimental evidence has shown that the prior-austenite grain size has a strong effect on the scale of packets and blocks and almost negligible effects on the lath substructure development [9][10][11][12]. This implies that the microstructure in the lath boundaries is practically independent of the prior-austenite grain size.…”
Section: Introductionmentioning
confidence: 92%
“…often noticed that a steel containing large austenite grains forms coarse martensite. For example, a tool steel with 0.39-C, 1.95-Cr, 0.27-Mo, 1.0-Ni (wt.%) was investigated after austenitisation at several temperatures from 900 °C to 1050 °C [49]. It was reported that the prior austenite grain size increased from 23.5 µm to 80 µm, which caused an increase in martensite packet size from 9.7 to 28.5 µm while the martensite lath width also increased from 0.60 to 0.69 µm.…”
Section: The Effect Of Austenitisation Temperaturementioning
confidence: 99%
“…However, in some studies, transgranular crack initiation and early short crack propagation along martensitic laths were also observed [15,19]. A frequently used explanation for intergranular crack initiation and early short crack propagation at PAGBs is the preferential formation of carbides [25][26][27][28][29][30][31][32] or segregations [25,26,[28][29][30][31] along microstructural interfaces. Further reasons are the impingement of slip bands at PAGBs [20,33,34] or the anisotropic elastic and plastic properties of the grains [17,18,21,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%